The trade direction of Malaysian wood and wood-based products in 2000 / Ahmad Fauzi Puasa and Ab. Rasip Ab. Ghani - Puasa, Ahmad Fauzi; Ab. Ghani, Ab. Rasip (Universiti Teknologi MARA Cawangan Pahang, 2003)
Wood and wood-based products play an important role in national income generation. Of the total 373.3 billion of national export in 2000, RM17.6 billion (4.7%) was derived from wood and wood-based products. This value was equivalent to that of RM17.4 billion (4.7%) generated by primary agricultural products. The six main wood products exported are sawntimber, sawlogs, veneer, plywood, furniture and moulding. Of the total RM17.6 billion of wood products exports in 2000, the share were 25% furniture, 22% plywood, 17% sawntimber, 14% logs, 5% moulding and 11%others wood products. The wood-based products export market destination depends on the products. Top Malaysian country markets for each of these wood products are identified and new potential markets suggested. For example, China is a potential market for sawntimber. Japan consumed the highest Malaysian wood and wood-based products from Malaysia, which amounted to RM 4.375 billion or 24.8% for 2000. USA was the second major importing country for Malaysian wood and wood-based products, which was RM 2.029 billion or 11.5%. These were followed by China RM 1.129 billion (6.4%), Taiwan RM 0.880 billion (5 %) and South Korea RM 0.738 billion (4.2%). The total export earning from the first five leading importers of wood and wood-based industries was about RM 9.153 billion or equivalent 51.9% of the total export. It is essential for Malaysia to at least maintain the traditional markets and in the meantime opening up new markets.